RDNA-12. THE FANCONI ANAEMIA (FA) PATHWAY AND GLIOBLASTOMA: A NEW FOUNDATION FOR DNA DAMAGE RESPONSE TARGETED COMBINATIONS. (11th November 2019) - Rominiyi, Ola; Myers, Katie; Gomez-Roman, Natividad; Lad, Nikita; Dar, Dawoud; Jellinek, David; Chalmers, Anthony; Carroll, Thomas; Chen, Beining; Al-Tamimi, Yahia; Collis, Spencer
Abstract: Treatment resistance in glioblastoma is underpinned by highly interconnected DNA damage response (DDR) processes. The FA-pathway is a fundamental DDR process required for the resolution of replication fork impeding lesions, and we have previously shown that it is inactive in normal brain, but is re-activated in glioblastoma, providing a cancer-specific target for combination DDR therapies. Here, we find that elevated FA-pathway gene expression in gliomas is associated with poor survival (-17.1% 5-year OS, p < 0.0001, n=329–REMBRANT). Furthermore, patient-derived glioblastoma stem cell (GSC) populations, which drive therapeutic resistance, display high FA-pathway expression relative to paired bulk tumour cell populations (mean 2.3-fold higher across genes, p =0.0073). We further show that inhibition of a single DDR process (FA-pathway, PARP, ATR or ATM) increases the susceptibility of glioblastoma cell lines and patient-derived GSCs to current adjuvant therapy. Importantly, clinically approved PARP inhibitor (PARPi) monotherapy stimulates robust FANCD2 mono-ubiquitination, supporting a role of FA-pathway activation in response to current DDR-targeted therapy. In clinically-relevant 3D GSC models, simultaneous inhibition of the FA-pathway (FAPi) and PARP or ATR enhanced temozolomide sensitisation compared to a single DDR inhibitor (DDRi). Furthermore, combined FAPi+PARPi consistently conferred radiosensitisation whilst combined FAPi+ATRi led to a profoundly radiosensitising effect; e.g. sensitizer enhancement ratio (SER 0.37 ) of 3.23 (3.03–3.49, 95% CI). Furthermore, comparison of α/β ratio enhancement suggests dual-DDRi strategies fundamentally alter the response of GSCs, whilst single cell gel electrophoresis & immunofluorescence studies suggest FA-pathway based DDRi combinations profoundly delay the resolution of IR-induced DNA strand breaks at 6 hours post-treatment, with increased persistent DNA double strand breaks at 24 hours. In conclusion, simultaneously targeting the FA-pathway and interconnected DDR processes represents an appealing therapeutic strategy. Additionally, constitutive lack of FA pathway function in some tumours, could serve as a novel predictive biomarker for patient response to PARPi and ATRi currently in clinical trials.